2019
DOI: 10.1038/s41438-019-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis uncovers the regulatory functions of long noncoding RNAs in fruit development and color changes of Fragaria pentaphylla

Abstract: To investigate the molecular mechanism underlying fruit development and color change, comparative transcriptome analysis was employed to generate transcriptome profiles of two typical wild varieties of Fragaria pentaphylla at three fruit developmental stages (green fruit stage, turning stage, and ripe fruit stage). We identified 25,699 long noncoding RNAs (lncRNAs) derived from 25,107 loci in the F. pentaphylla fruit transcriptome, which showed distinct stage- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…Of these, 63.29% were lincRNAs, which was similar to the proportion of lincRNAs in rice 48 . The lncRNAs were shorter than known mRNAs as previously reported in other plants 49 , also the average number of exons was less.…”
Section: Discussionsupporting
confidence: 71%
“…Of these, 63.29% were lincRNAs, which was similar to the proportion of lincRNAs in rice 48 . The lncRNAs were shorter than known mRNAs as previously reported in other plants 49 , also the average number of exons was less.…”
Section: Discussionsupporting
confidence: 71%
“…In angiosperms, lncRNAs participate in fruit development and color change in strawberry [ 33 ], as well as aroma formation in black tea [ 34 ]. In gymnosperms, lncRNAs have an important role in the regulation of leaf development [ 27 ] and leaf color changes in G. biloba [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some lncRNAs interact with microRNAs (miRNAs), serving as miRNA precursors or competing endogenous RNAs (ceRNAs) to serve as decoys for specific miRNAs, thus protecting the target mRNAs from repression [29][30][31][32] . In recent years, several studies have indicated that lncRNAs play important roles in various biological processes in plants, including roles in organ development, nutrient metabolism, male sterility, and plant immunity [33][34][35][36][37] . In particular, lncRNAs are considered essential regulators of the response to biotic and abiotic stresses in plants 30,[38][39][40] .…”
Section: Introductionmentioning
confidence: 99%